Cross-phosphorylation of bacterial serine/threonine and tyrosine protein kinases on key regulatory residues - Shi, Lei; Pigeonneau, Nathalie; Ravikumar, Vaishnavi; Dobrinic, Paula; Macek, Boris; Franjevic, Damjan; Noirot-Gros, Marie-Francoise; Mijakovic, Ivan (Frontiers in Microbiology, 2014)
Bacteria possess protein serine/threonine and tyrosine kinases which resemble eukaryal kinases in their capacity to phosphorylate multiple substrates. We hypothesized that the analogy might extend further, and bacterial kinases may also undergo mutual phosphorylation and activation, which is currently considered as a hallmark of eukaryal kinase networks. In order to test this hypothesis, we explored the capacity of all members of four different classes of serine/threonine and tyrosine kinases present in the firmicute model organism Bacillus subtilis to phosphorylate each other in vitro and interact with each other in vivo. The interactomics data suggested a high degree of connectivity among all types of kinases, while phosphorylation assays revealed equally wide-spread cross-phosphorylation events. Our findings suggest that the Hanks-type kinases PrkC, PrkD and YabT exhibit the highest capacity to phosphorylate other B. subtilis kinases, while the BY-kinase PtkA and the two-component-like kinases RsbW and SpoIIAB show the highest propensity to be phosphorylated by other kinases. Analysis of phosphorylated residues on several selected recipient kinases suggests that most cross-phosphorylation events concern key regulatory residues. Therefore, cross-phosphorylation events are very likely to influence the capacity of recipient kinases to phosphorylate substrates downstream in the signal transduction cascade. We therefore conclude that bacterial serine/threonine and tyrosine kinases probably engage in a network-type behavior previously described only in eukaryal cells.